Overcoming the Innovator's Dilemma through Organisational Ambidexterity within the Indian Pharmaceutical Industry - Pai, Ashwin (2007)
ABSTRACT Firms face a difficult challenge to manage transition to new technologies,markets and regulatory policies. Technological or institutional change have proven to be a cause for failure of established firms as these firms have failed to adapt to such new environments. The Trade Related intellectual property rights (TRIPs) agreement is one such institutional change for research intensive industries from developing countries. In the past, firms within the developing countries operated under weak patent laws backed by the host government in order to protect their domestic industry. However, as a result of the TRIPs agreement, firms within developing countries like India will have to operate under an environment of stronger intellectual property. This dissertation therefore investigates the learning strategies involved in development of innovative R&D capabilities within Indian pharmaceutical firms as a response to rapid technological change and changing regulatory policies. In order to develop these new capabilities, firms within the Indian pharmaceutical industry have had to acquire new knowledge and then combine it with existing knowledge bases to adapt and survive in this new regulatory environment. The investigation revealed that some Indian firms have created knowledge and acquired innovative abilities through in-house activities and, through alliances with Indian and overseas research institutes. The Indian pharmaceutical firms' response provides insights which have important implications for similar firms from other developing countries.